A Framework to Support IT Outsourcing Process Decision - Yap, Chee Cheng (2004)

(untitled)
The paper will study the IT outsourcing process decision and developed a theoretical framework consisting of seven phases of IT outsourcing process decision. The framework consists of initial outsourcing decision phase, analysis and planning phase, design outsourcing management phase, selecting IS supplier phase, implementing phase, monitor outsourcing relationship and evaluating phase. Meanwhile the study of the project also identifies the critical success factors should be pay attention during the process of IT outsourcing activities. The methodology chooses to use to develop framework began with the literature review on the previous journal and the research paper. Meanwhile the data for this study is also drawn from a mixture of questionnaires and semi-structured interviews administered to multiple recipients at banking institutions. Basically, the questions cover general issues of IT management in the firm such as the methodology for identifying and evaluating projects, developing business plans the approval process, and their project management guidelines. The reason to provide a IT outsourcing process framework is to ensure organization achieve the desire benefits from the outsourcing activities. Beside, outcome of the study also expected to alert organizations to the strategic issues along with a comprehensive cost analysis that should be considered if an effective IT outsourcing process framework is eventually formulated.